Analysis of nuclear-renewable hybrid energy system for marine ships. (November 2021) - Gabbar, Hossam A.; Adham, Md. Ibrahim; Abdussami, Muhammad R.
Abstract: While several actions are being taken to reduce Greenhouse Gas (GHG) emissions from land-based transportation, marine transportations are often unnoticed. Ocean-going marine ships are accounted for a large amount of global GHG emissions. Renewable Energy Sources (RESs) are free from GHG emissions and playing an important role in sustainable development by lessening GHG emissions. Integration of RESs in ocean-going marine ships could be an option to make marine transportation free from emissions. Ocean-going marine ships require a large amount of reliable energy to support the propulsive load demand. RESs are intermittent, and a large amount of energy cannot be stored economically by the available energy storage techniques. Additionally, the penetration of RESs in a marine ship is limited by the available area and total weight carrying capacity of that marine ship. Because of these limitations of RESs in marine ships, there is a requirement of integrating other types of energy sources with RESs to support the baseload energy demand and to avoid the variableness of RESs. Conventional fossil fuel-based generators, like diesel generators, can be incorporated with RESs to overcome these shortcomings of RESs. However, as the penetration of RESs is limited to marine ships, most of the energy is supplied by fossil fuel-based generators. Therefore, the integration of RESs with fossil fuel-based generators merely reduces GHG emissions and is not a feasible option to make marine ships free from emissions. Fossil fuel-based generators need to be replaced by emissions-free and reliable energy sources to make the marine ships free from emissions. Small scale nuclear reactors, such as Small Modular Reactors (SMRs) and Microreactors (MRs), are free from GHG emissions and are competitive candidates to replace fossil fuel-based generators. In this paper, four different energy systems have been analyzed for marine ships namely 'Stand-alone Fossil Fuel-based Energy System', 'Stand-alone Nuclear Energy System', 'Renewable and Fossil Fuel-based Hybrid Energy System' and 'Nuclear-Renewable Hybrid Energy System (N-R HES)' in terms of certain Key Performance Indicators (KPIs). The KPIs include the Cost of Energy (COE), Net Present Cost (NPC), and GHG emissions. The results show that the N-R HES could be the best energy system for the marine industry to reduce GHG emissions and improve economic performance. A sensitivity analysis is also carried out by changing certain parameters to reinforce the findings of this study.